Ellipsomyxa gobii (Myxozoa: Ceratomyxidae) in the common goby Pomatoschistus microps (Teleostei: Gobiidae) uses Nereis spp. (Annelida: Polychaeta) as invertebrate hosts - Køie, Marianne; Whipps, Christopher M; Kent, Michael L (Folia parasitologica, 2004)
Nereis diversicolor O.F. Müller and N. succinea Frey et Leuckart (Polychaeta, Nereidae) living in brackish shallow areas in Denmark are naturally infected with tetractinomyxon actinospores. Infected Nereis spp. were experimentally fed to various potential fish hosts, and the actinosporean stages developed into myxosporean stages of Ellipsomyxa gobii Køie, 2003 (Ceratomyxidae) in the gallbladder of the common goby Pomatoschistus microps (Krøyer) (Gobiidae). The European eel Anguilla anguilla (L.), three-spined stickleback Gasterosteus aculeatus L., small sand eel Ammodytes tobianus L., flounder Platichthys flesus (L.), European plaice Pleuronectes platessa L. and common sole Solea solea (L.) did not become experimentally infected. In Danish shallow brackish areas P. microps is naturally infected with E. gobii, in some areas with a prevalence >90%. We compared small subunit ribosomal DNA sequences of the actinosporean with E. gobii from P. microps. Sequences were identical, which further verifies that both forms belong to the same organism. This is the first myxozoan two-host life cycle in the marine environment.
Keywords: stadia vývoje; Microscopy, Phase-Contrast; Gallbladder; Sequence Analysis, DNA; Dánsko; protozoální DNA; DNA, Protozoan; zvířata; Eukaryota; žlučník; mikroskopie fázově kontrastní; sekvenční analýza DNA; RNA ribozomální; Denmark; Microscopy, Interference; RNA, Ribosomal; polymerázová řetězová reakce; interferenční mikroskopie; Polymerase Chain Reaction; Life Cycle Stages; Polychaeta; Animals; Perciformes